2018
DOI: 10.1007/s11019-018-9871-9
|View full text |Cite
|
Sign up to set email alerts
|

Research ethics aspects of experimentation with LSD on human subjects: a historical and ethical review

Abstract: In this paper our aim is to examine whether research conducted on human participants with LSD-25 (lysergic acid diethylamide) raises unique research ethical questions or demands particular concerns with regard to the design, conduct and follow-up of these studies, and should this be the case, explore and describe those issues. Our analysis is based on reviewing publications up to date which examine the clinical, research and other uses of LSD and those addressing ethical and methodological concerns of these ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Various studies have demonstrated improvement in humans after being exposed to these drugs. Some of the medications that have been shown to decrease depression and anxiety are LSD [ 52 ], peyote [ 58 ], ketamine [ 67 ], arketamine [ 24 , 63 ], N, N-dimethyltryptamine [ 11 ], psilocybin [ 64 ], and deuterated etifoxine [ 59 , 60 ]. Administration of 5-methoxy-N, N-dimethyltryptamine (5-MeO-DMT) has reduced suicidal ideations, planning, and attempts [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have demonstrated improvement in humans after being exposed to these drugs. Some of the medications that have been shown to decrease depression and anxiety are LSD [ 52 ], peyote [ 58 ], ketamine [ 67 ], arketamine [ 24 , 63 ], N, N-dimethyltryptamine [ 11 ], psilocybin [ 64 ], and deuterated etifoxine [ 59 , 60 ]. Administration of 5-methoxy-N, N-dimethyltryptamine (5-MeO-DMT) has reduced suicidal ideations, planning, and attempts [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…These side effects can vary from mental state/consciousness alterations to physiological changes. The following are the general risks of consumption of these compounds: LSD includes delusions, visual hallucinations, distortion of one’s sense of time and identity, impaired depth and time perception, artificial sense of euphoria or certainty, distorted perception of the size and shape of objects, movements, colors, sounds, touch, and the user’s body image, severe, terrifying thoughts and feelings, fear of losing control, fear of death, and panic attacks [ 52 ]. Reports of 5-MeO-DMT show agitation and tachycardia with periodic reports of hyperthermia, seizures, coma, increased serum creatinine, and life-threatening experiences, such as cardiac arrest and possible death [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychedelika erhöhen die Suggestibilität und führen zu einem vulnerablen mentalen Zustand. Dies macht Patienten anfällig für möglichen Missbrauch durch Behandler [5]. Nach der Einnahme neigen Patienten und Probanden dazu, körperliche Berührungen und sexuelle Annäherungsversuche möglicherweise weniger abzulehnen und sich auf Verhaltensweisen einzulassen, die sie später als Missbrauch erkennen könnten.…”
Section: Systemische Aspekteunclassified
“…The possibility of including LSD as a psychotherapy option requires information about its metabolism, pharmacology, and pharmacokinetics. The development of studies in humans address ethical issues such as the patient's vulnerability to addiction, and evaluation of risks and benefits, which must be well described, supervised, and managed precisely [15,16]. Thus, the use of the nematode Caenorhabditis elegans (C. elegans), a widely applied model in neurological studies [17,18,19,20,21], and represents an alternative to corroborate studies with humans.…”
Section: Introductionmentioning
confidence: 99%